Evaluation of the Convergence Region of an Automated Registration Method for 3D Laser Scanner Point Clouds - Kwang-Ho Bae (Sensors, 2009)
Using three dimensional point clouds from both simulated and real datasets from close and terrestrial laser scanners, the rotational and translational convergence regions of Geometric Primitive Iterative Closest Points (GP-ICP) are empirically evaluated. The results demonstrate the GP-ICP has a larger rotational convergence region than the existing methods, e.g., the Iterative Closest Point (ICP).